ANALYSIS OF EFEECTIVENESS OF CRITICAL CONTROL IMPLEMENTATION USING PLANNED JOB OBSERVATION IN DIVISION X PT. A - Kurniawan, Ahmad Tahta; Djunaidi, Zulkifli (LPPM STIE Muhammadiah Bandung, 2024)
International Council of Mining and Metals (ICMM) constructed a framework of Critical Control Management (CCM) to prevent fatality. PT A still experienced the accident with TRIR 0.168 in 2020 then increased 0.176 in 2021. This study aimed to assess the effectiveness of CC in Mining Industry Division X PT A. Semi-quantitative study with descriptive model conducted in Division X PT. A. Data collected according to 5 main variables, namely supervisory system, hierarchy of control implementation, control implementation, policy conformity, and hazards and risks compliance. Primary data was collected from 17 supervisors who had Planned Job Observation (PJO) responsibility through questionnaire and in-depth interviews. Secondary data was HIRADC collected from 11 departments. Data analysis was conducted by descriptive statistical analysis and content analysis. PJO result indicated 20.9% inadequate result related to work practice. Control effectiveness questionnaire signified adequate result for all 5 variables with very suitable result. In addition, in-depth interviews resulted in positive findings in all variables and negative findings for supervisory system, hierarchy of control implementation, and control implementation. Overall, the effectiveness of CC in Division X PT. A still needs to be improved, especially for the aspects of work practice control enforcement and workers’ attitude towards CC.